Leading with Agility: Empowering Engagement and Performance in the Hybrid Workforce - Ghozali, Ghozali; Agustina, Ratna; Cahyani, Diah (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This study investigates the impact of agile leadership and employee engagement on performance within a hybrid workforce, specifically focusing on freelance workers on the Upwork platform. Utilizing a quantitative research design, data were collected from 50 freelancers through online questionnaires and analyzed using Smart PLS for path analysis. The findings reveal significant positive relationships: agile leadership positively influences the effectiveness of the hybrid work model, which in turn enhances performance. Additionally, employee engagement was found to significantly impact performance through its contribution to the hybrid work model's effectiveness. These results underscore the importance of agile leadership and employee engagement in optimizing performance in hybrid work settings. The study provides valuable insights for organizations aiming to foster a productive and collaborative environment among freelance workers, highlighting the need for leaders to adapt their practices to meet the unique challenges of the hybrid workforce.